(untitled) (Academia Science Repository, 2023)
This article presents the benefits of maintaining biological diversity among agricultural crops, rational use of natural resources, and growing organic agricultural products in farming systems. As the world population’s demand for cheap and high-quality food products is increasing year by year, organic agriculture is widely used all over the world. Therefore, further improvement of organic farming in farmers, peasants and households of our country leads to great efficiency. Below are the advantages of organic agriculture, the challenges faced during its implementation and the future of this practice.